2019
DOI: 10.3390/microorganisms7120699
|View full text |Cite
|
Sign up to set email alerts
|

Cold Adapted Nitrosospira sp.: A Potential Crucial Contributor of Ammonia Oxidation in Cryosols of Permafrost-Affected Landscapes in Northeast Siberia

Abstract: Permafrost-affected landscape soils are rich in organic matter and contain a high fraction of organic nitrogen, but much of this organic matter remains inaccessible due to nitrogen limitation. Microbial nitrification is a key process in the nitrogen cycle, controlling the availability of dissolved inorganic nitrogen (DIN) such as ammonium and nitrate. In this study, we investigate the microbial diversity of canonical nitrifiers and their potential nitrifying activity in the active layer of different Arctic cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 89 publications
(71 reference statements)
1
24
0
Order By: Relevance
“…Nitrosospira is a typical AOB and lives in various environments [54,55]. Although typical Nitrosospira like those in domestic wastewater treatment plants prefers warmer growing environment (25°C to 30°C) [56], a recent study had found certain species of Nitrosospira could adapt and enrich in the cold environment [53], and our results consolidated this finding. Additionally, Methylomonas is the plausible AOB in permafrost.…”
Section: The Nitrogen Cyclessupporting
confidence: 81%
See 1 more Smart Citation
“…Nitrosospira is a typical AOB and lives in various environments [54,55]. Although typical Nitrosospira like those in domestic wastewater treatment plants prefers warmer growing environment (25°C to 30°C) [56], a recent study had found certain species of Nitrosospira could adapt and enrich in the cold environment [53], and our results consolidated this finding. Additionally, Methylomonas is the plausible AOB in permafrost.…”
Section: The Nitrogen Cyclessupporting
confidence: 81%
“…Nitrosospira were the active ammonia‐oxidizing bacteria (AOB) within the community of thawed permafrost, while no AOB could be identified in frozen permafrost soil, suggesting clear repression of AOB activity in frozen permafrost. We could not detect active ammonia‐oxidizing archaea (AOA) in permafrost and such AOB‐dominated nitrogen metabolism was also observed in research in cold environments like high‐altitude lakes [52] and permafrost in northeast Siberia [53]. Nitrosospira is a typical AOB and lives in various environments [54,55].…”
Section: Resultsmentioning
confidence: 83%
“…There are some studies on N cycling in permafrost-affected soils (e.g., Biasi et al 2005 ; Stewart et al 2014 ; Sanders et al 2019 ; Horn and Hetz 2021 ). Recent newer studies focus on the potential nitrous oxide (N 2 O) emissions from permafrost-affected soils (reviewed by Voigt et al ( 2020 )) and the input of C and N into the fluvial system (Hugelius et al 2020 ; Pastor et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing nitrate flux supports the hypothesis that permafrost thaw routes subsurface flow through deeper, mineral‐rich soil layers (Bowden et al, 2008; Keller, Blum, & Kling, 2010), providing access to biologically available N released with thaw (Keuper et al, 2012). Nitrification is widespread in Arctic soils and rivers (Harms et al, 2016; Lafrenière, Louiseize, & Lamoureaux, 2017; Sanders, Fiencke, Hüpeden, Pfeiffer, & Spieck, 2019) and can proceed rapidly (Peterson et al, 2001; Snyder & Bowden, 2014). While nitrate uptake is important in Arctic streams, the portion of the nitrate pool that is removed by uptake per unit time is relatively small, allowing nitrate to travel further downstream (Peterson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%